Layering pattern effects on vibrational behavior of coconut sheath/banana fiber hybrid composites. (15th January 2016) - Senthil Kumar, K.; Siva, I.; Rajini, N.; Winowlin Jappes, J.T.; Amico, S.C.
Abstract: Two different fibers, namely short banana (B) and naturally woven coconut sheath (C), were hybridized in polyester matrix composites using compression molding. Various composites were produced with the same overall fiber wt.% and varying the relative wt.% of the individual fibers. Banana and coconut sheath fibers were surface treated using 1 N alkali solution to enhance interfacial adhesion. Static mechanical and dynamic characteristics such as natural frequency and damping were studied and impulse hammer technique was employed to study the dynamic characteristics of the composites. Mechanical performance was maximized for the highest relative amount of banana fiber in the composites. The mechanical properties were also found to vary with the layering pattern. Irrespective of the relative wt.% of fibers and layering pattern used, alkali treatment showed a positive effect on the evaluated properties. The CBC layering pattern exhibited the greatest damping, indicating better energy absorption capability brought by the porous structure of the coconut sheath fiber. Graphical abstract: Highlights: Layering pattern imparts stiffness difference in hybrid composites. Skin-eccentric type of composite exhibits better tensile and flexural properties. Alkali treatment of fibers enhances energy distribution during impact loading. Stacking sequence can significantly enhance damping values.